STRATEGI BERTAHAN HIDUP BURUH PEREMPUAN INDUSTRI PERMEN DI DESA AMPELDENTO, DUSUN CURAHAMPEL KECAMATAN PAKIS KABUPATEN MALANG - Nita Indah Lestari; Amanah Agustin (CV. ADIBA AISHA AMIRA, 2023)
Industry is one sector that has an important role in regional development. The industries that are located around the countryside make a change in social mobility for the people around the countryside. Where this social mobility continues to occur and develop in traditional society towards modern society. According to Pitirim A Sorokin, social mobility is a form of transfer of status and role of a person or group of people from a higher social class to a lower social class (Setiadi, 201:503). For example, a housewife whose livelihood is a farmer switches to a livelihood as an industrial worker. This social status change experienced by a person or group of people in the social structure of society is called social mobility. Rural women, especially housewives who are factory or industrial workers, are very much in demand to increase their income to meet household needs to help their husbands. For rural families, being a woman factory or industrial worker, of course, works hard to help men as the head of the household to fulfill the economy in the family, where income as a factory or industrial worker is considered to be able to help the economy in the household which is one of the strategies for survival. life. Women in rural areas are not only housewives but also work in any sector and are involved in various activities such as factory workers or industries that are developing in rural areas